Parents as students: seeking for the balance - Damianidou, Eleni (International Journal about Parents in Education, 2023)
The purpose of this study was to examine the potential impact of the conflict between work, family and school on absenteeism from high-school, and the role academic motivation might have, for non-traditional students in Cyprus. To this end, a mixed-method research was conducted. The main research tools were the structured interview with former and current nontraditional high-school students with dropout behavior and a structured questionnaire for the registered students of a second chance school in Cyprus. Thematic analysis of the interview data indicated that being unable to respond effectively to the complex role of simultaneously being a parent, an employee and a student had resulted to increased absenteeism and dropout. Statistical analysis confirmed the above view, since absenteeism had a positive correlation with working hours and having children. Moreover, it was found that almost half of the participants experienced work-family-school conflict. Intention to dropout was higher for students that experienced work-family-school conflict compared to those who did not. It is noteworthy that academic motivation could predict intention to dropout. In conclusion, it seems that being a parent, a worker and a student is not an easy job, since it may result to work-family-school conflict and school dropout. However academic motivation may mediate the above relationship, increasing the likelihood of non-traditional students graduating from high-school.